History´s humanist fiction: Review of Miguel Baraona Cockerell´s novel “Culpeo” - Sancho Ugalde, María De los Ángeles (2018)
This review of the work by the writer Miguel Baraona Cockerell (Culpeo. 2015. San José-CostaRica: EUNA), seeks to situate this novel within the analytical framework provided both by thestudy of historical fiction and the humanist though developed by this author in other works.